Optimization of Digital Marketing and Social Media Strategies in Promoting Tourist Attractions in Mount Puntang, Campakamulya Village, Cimaung District, Bandung Regency - Bethani Suryawardani; Astri Wulandari; Riska Aprilina; Wingga Nayshila Aura Putri; Sabitah Meilina Raharjo; Nailla Agnia Noor Syiwan (International Journal Of Community Service, 2026)
Campakamulya Village has promising natural tourism potential, particularly in the Gunung Puntang tourist area. However, this potential has not been optimally utilized through digital media. The main challenges faced by the partners include limited understanding of digital marketing strategies, suboptimal social media management, and the lack of consistency in content and visual identity of the tourist destination. This community service activity aims to enhance the capacity of destination managers and local communities in optimizing social media marketing and digital marketing strategies. The implementation methods include training, workshops, mentoring, and the direct application of digital content strategies. The results indicate an improvement in participants’ understanding of social media management, content strategy, copywriting, and the utilization of Search Engine Optimization (SEO). Furthermore, the implementation of the proposed strategies resulted in increased audience interaction and engagement on the social media platforms of the Gunung Puntang tourist destination. This activity is expected to provide a sustainable impact in supporting digital- based rural tourism promotion.